2012
DOI: 10.3109/00365521.2012.719924
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of hepatic manifestation in Wilson disease with transient elastography, ARFI, and different fibrosis scores

Abstract: TE displayed a gradual increase between different stages of hepatic manifestation in WD and could significantly discriminate cirrhosis. The TE cutoff for cirrhosis may be clinically more relevant than the R-ARFI value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…In contrast, Sini et al, 25 in a study of 35 WD patients, identified an 8.4-kPa cutoff for the discrimination of severe fibrosis, and Karlas et al 14 found an even lower cutoff, 6.1 kPa, for the identification of cirrhosis. These lower cutoffs for severe and significant fibrosis than those reported for other etiologies 3,17 stress the fact that elastographic values may depend on the cause of the liver disease.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast, Sini et al, 25 in a study of 35 WD patients, identified an 8.4-kPa cutoff for the discrimination of severe fibrosis, and Karlas et al 14 found an even lower cutoff, 6.1 kPa, for the identification of cirrhosis. These lower cutoffs for severe and significant fibrosis than those reported for other etiologies 3,17 stress the fact that elastographic values may depend on the cause of the liver disease.…”
Section: Discussionmentioning
confidence: 96%
“…14, 24 Karlas et al, 14 citing a study published in 1980, 27 suggest focal hepatic accumulation as an etiology-specific feature that may influence LS in WD; furthermore, they hypothesized that these differences between WD patients and groups of patients with other etiologies may be the result of several study-specific characteristics and diseasespecific properties, such as clinical scoring systems being used to classify the degree of hepatic involvement rather than histologic criteria. 1,2,14 They also mentioned that the patients in their study group had already been undergoing longterm treatment for WD and most had had a stable disease course after the initial improvement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations